2014
DOI: 10.1074/jbc.m114.555060
|View full text |Cite
|
Sign up to set email alerts
|

Induction of p21CIP1 Protein and Cell Cycle Arrest after Inhibition of Aurora B Kinase Is Attributed to Aneuploidy and Reactive Oxygen Species

Abstract: Background: p21 is induced when Aurora B is inhibited. Results: p21-induction after Aurora B inhibition is attributed to aneuploidy and reactive oxygen species. Conclusion: Aneuploidy and ROS mediate cell cycle arrest after Aurora B inhibition by promoting p21-induction. Significance: The study contributes to the understanding of the mechanisms for p21-induction and cell cycle arrest following an aberrant mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
(52 reference statements)
3
22
1
Order By: Relevance
“…Aurora A and Aurora B are known to phosphorylate and inactivate p53 in cultured cells, resulting in decreased expression of its transcriptional targets (24,25,46). Indeed, Aurora B deficiency leads to enhanced expression of p21 Cip1 , resulting in aberrant Cdk activity and cell cycle progression (26,47). These results are also in agreement with an inverse correlation between Aurora B and p21…”
Section: Discussionsupporting
confidence: 79%
“…Aurora A and Aurora B are known to phosphorylate and inactivate p53 in cultured cells, resulting in decreased expression of its transcriptional targets (24,25,46). Indeed, Aurora B deficiency leads to enhanced expression of p21 Cip1 , resulting in aberrant Cdk activity and cell cycle progression (26,47). These results are also in agreement with an inverse correlation between Aurora B and p21…”
Section: Discussionsupporting
confidence: 79%
“…A study suggested that phosphorylation of p38 MAPK was induced by ROS following by ZM447439 (a selective inhibitor of Aurora B kinase) treatment, while no change in expression of g-H2AX could be detected. 20 Inhibition of Aurora A induced DNA damage and increased the accumulation of g-H2AX in cancer cells. 18 In this study, treatment of VX680 induced apoptosis and activated H2AX in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] In recent studies, the activation of p38 MAPK has been suggested to be induced by Aurora B kinase inhibition. 37,38 However, the role of p38 MAPK in VX680-induced effects remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that AKT3 suppresses AURKi-induced caspase-9 activation and confers resistance to AURKi, whereas the AURKi-induced accumulation of TP53 and P21 was not abolished by AKT3. A previous study reported that reactive oxygen species (ROS) and p38 MAPK activate P21 in AURKiinduced aneuploid cells (34), and the increased ROS production in aneuploid cells is attributed to high glucose metabolism (35). Intriguingly, the glucose metabolic pathway seems to be altered in our AURKi-resistant clones, because the expressions of the glucose transporter GLUT1 and some glycolysis-regulating enzyme genes were up-regulated in the VX-resistant clones (data not shown).…”
Section: Discussionmentioning
confidence: 84%